The C'nano competence centres. (16th June 2008) - Fontaine, Alain; Robert, Jean-Louis; Menand, Alain
Nanoscience has been increasingly supported in France over the years by the Directorate of Research of the Ministry which established in 2004 the National Nanoscience Program, in cooperation with the major research organisations CNRS and CEA. The creation of five centres of competence, known as C'Nano, one per major French geographical region, ensures networking among the regional facility centres and allows a clear, consolidated information base to be established, available for sponsorship, regional authorities and industrial partners. The C'Nano centres are the optimising and coordinating tools needed by the French laboratories engaged in the rapid development of nanoscience.